Efisien Epidemic: Pemilihan jarak terjauh dan arah pergerakan kendaraan untuk pendistribusian pesan darurat pada VDTN - Akbi, Denar Regata; Wibisono, Waskitho (Universitas Muhammadiyah Malang, 2016)
AbstractVANET has characteristics of high mobility vehicles and fast changes of the topology, it causes process data communication interrupted frequently. It can be minimized by Vehicular Technology Delay Tolerant Networking (VDTN). The Epidemic protocol is one of which was used to the distribution of message on VANET, the mecanism of Epidemic protocol caused amount of message, thus impacting in distribution unefficient message and the performance can be lower.The porposed of this research are to solve the problem of Epidemic protocol, namely e-Epidemic protocol. This proposed protocol are the development of Epidemic protocol that give more attention on the vehicles direction and farest vehicle.The results based on the number of messages distribution showed the number of messages average which owned e-Epidemic protocol is 8% whereas epidemic protocol is 92%. And based on the delay value, e-Epidemic protocol only has delay as much as 17%, meanwhile epidemic protocol has delay 83%.